2017
DOI: 10.1186/s40001-017-0255-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbonyl sulfide in acute lung injury following limb ischemia/reperfusion in rats

Abstract: ObjectiveTo investigate the effect of carbonyl sulfide (COS) on limb ischemia/reperfusion (I/R)-induced acute lung injury (ALI) and the associated mechanism in rats.MethodsALI was induced by bilateral hind limb I/R in Sprague–Dawley (SD) rats. Sixty-four SD rats were randomly divided into the control group, I/R group, I/R + COS group, and I/R + AIR group. We observed the survival rate of the rats and the morphological changes of lung tissues, and we measured the change in the lung coefficient, the expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Inflammatory factors in the ischemic area and the extensive release of oxygen free radicals cause damage to distal organs and the lung is particularly susceptible to acute injury (22). Previous studies on animal models have demonstrated that the expression levels of inflammatory cytokines, such as TNF-α, IL-1, IL-6 and IL-8, are significantly increased after limb i/r (23)(24)(25). The occurrence of acute lung injury is closely related to the activation of various inflammatory factors; the extensive release of inflammatory cytokines is one of the most important factors that ultimately leads to the onset of systemic inflammatory response syndrome (24).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory factors in the ischemic area and the extensive release of oxygen free radicals cause damage to distal organs and the lung is particularly susceptible to acute injury (22). Previous studies on animal models have demonstrated that the expression levels of inflammatory cytokines, such as TNF-α, IL-1, IL-6 and IL-8, are significantly increased after limb i/r (23)(24)(25). The occurrence of acute lung injury is closely related to the activation of various inflammatory factors; the extensive release of inflammatory cytokines is one of the most important factors that ultimately leads to the onset of systemic inflammatory response syndrome (24).…”
Section: Discussionmentioning
confidence: 99%
“…It was found in the physical experiment that cytokines, TNF-α, IL-1, and IL-6 were significantly changed when I/R was applied to limbs. 10 12 Therefore, the occurrence of acute lung injury is closely related to the activation of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence shows that endoplasmic reticulum stress (ERS) induces the cell dysfunction following reperfusion . There is an evidence showing that carbonyl sulfide as a biological gas signaling molecule has the protective effect on lung injury after LIR . HO family has two distinct isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…28 There is an evidence showing that carbonyl sulfide as a biological gas signaling molecule has the protective effect on lung injury after LIR. 29 HO family has two distinct isoforms. HO-1 expression is stimuli inducible but HO-2 shows constitutive expression.…”
Section: Discussionmentioning
confidence: 99%